The effect of problem based learning (PBL) model on fourth-grade students’ learning outcomes of data presentation - Dwi Kartika Sari; Yarisda Ningsih (Journal Of Teaching And Learning In Elementary Education, 2023)
The purpose of this study was to determine the effect of the Problem Based Learning model on the learning outcomes of data presentation in the form of a bar diagrams in Class IV SDN Cluster II, Lubuk Kilangan District, Padang City. This research is a quantitative research with the type of quasi-experimental research design. Using purposive sampling technique, we obtained 24 students from class IVA SDN 09 Bandar Buat as the experimental class and 25 students from class IVB SDN 09 Bandar Buat as control class. The results showed that the average experimental class was 82,81 and control class 69.50. The results of the t-test calculation with a significance level of 0.05 obtained tcount > ttable is 4.493 > 2.012, then H0 is rejected and H1 is accepted. The N-Gain test in the experimental class obtained an average of 0.67 while in the control class obtained an average of 0.43. So it can be concluded that the Problem Based Learning model has an effect on learning outcomes in presenting data in the form of bar diagrams in class IV SDN Cluster II, Lubuk Kilangan District, Padang City.